Growth kinetics of MPS-capped CdS quantum dots in self-assembled thin films - Koc, Kenan; Tepehan, Fatma Z.; Tepehan, Galip G. (SPRINGEROPEN, 2012)
For this study, we prepared colloidal CdS quantum dots using 3-mercaptopropyltrimethoxysilane as capping agent. Colloidal CdS quantum dots were directly deposited on glass substrates by a spin-coating process. Coated substrates were heat-treated between 225A degrees C and 325A degrees C for various heat treatment time intervals to investigate the growth kinetics of the quantum dots. Results showed that sizes of the CdS quantum dots grew approximately from 2.9 to 4.6 nm, and the E (1s1s) energy values shifted approximately from 3.3 to 2.7 eV. Results showed that the average size of quantum dots increase by thermal treatment due to Ostwald ripening. The thermal process used to grow the size of quantum dots was examined according to the Lifshitz-Slyozov-Wagner theory. The activation energy of CdS quantum dots in thin films was calculated at approximately 44 kJ/mol.
Keywords: CdS quantum dots; 3-Mercaptopropyltrimethoxysilane; Growth kinetics; Ostwald ripening; Thin films; OPTICAL-PROPERTIES; SIZE; NANOPARTICLES; CLUSTERS; Science & Technology - Other Topics; Materials Science; Physics